고강도 볼트의 수소취성에 대한 민감도 측정방법 - 함종오; Jong Oh Ham; 김복기; Bok Gi Kim; 이선호; Sun Ho Lee (대한금속·재료학회지, 49(1), 2011)
To measure the sensitivity of the hydrogen embrittlement from plated high strength bolts (SWCH18A, F11T), the bolt was stressed by a corresponding to the amount of tensile strain of 5% and 20%, and then the bolt developed a crack on the surface. The bolt that didn`t have concentrated hydrogen, even though it was stressed by a corresponding the amount of tensile strain of 5% and 20%, no crack developed. However, the bolt that had concentrated hydrogen, developed cracks from the thread crest to the root. It is impossible to measure the hydrogen amount from plated high strength bolts using Hydrogen-Determinator, because of the limitation of the minimum sample size (about 1g as a mass or 5 × 5 × 5 mm3 as a volume). Therefore, the sensitivity of hydrogen embrittlement can be measured by observing the presence of cracks on the surface of plated high strength bolts which are stressed by a corresponding to the amount of tensile strain of 5% and 20%.